Morphological and Functional Abnormalities of the Thyroid Gland among End Stage Kidney Disease Patients - O Osman; T Alnaemi; S Alneel; F Qayyum; M Abdalla; A Makeen; B Griffith (Journal of Hematology and Oncology Research, 2016)
Several interactions exist between thyroid and kidney function in many disorders. Many publications explored the relationship between thyroid diseases (TD) and chronic kidney diseases (CKD). However, the morphological thyroid changes in patients with CKD or End Stage Kidney disease (ESKD) were not fully explored. The aim of this study is to explore the morphological and the functional abnormalities of the thyroid gland among ESKD patients as detected by Doppler ultrasound. Patients and Methods: All of the 92 ESKD patients at our center were consented and included in the study. Demographic and clinical data and biochemical and hormonal profiles were recorded. Every patient received a dedicated ultrasound scan of the thyroid gland. GE ultrasound system with Doppler capabilities and high frequency transducer was used. Grey scale imaging and Doppler ultrasound were used to image the thyroid gland for every patient. Taking the thyroid morphology detected by ultrasound and the thyroid function as the dependent variables, all other parameters of age, sex, BMI, occupation, residence, duration of time on dialysis and other comorbilities were taken as independent variables and their relationship to the dependent variables was further studied using appropriate statistical tests. Results: Thyroid nodule(s) presence was found to be the most prevalent thyroid morphology detected on ultrasound scanning. Fifty three patients (57.6%) were found to have ultrasound detected nodule(s). The nodule presence was correlated to different independent variables and was found to significantly correlate with age only. The thyroid function as reflected by the level of thyroid hormones was also studied for correlation with the independent variables. No correlation was found between the thyroid function and the presence of nodules. Conclusion and Recommendation: Ultrasound detected nodules are very common in ESKD patients. The presence of nodule significantly correlates with patient age denoting its degenerative nature. Ultrasound screening of the thyroid in ESKD patients may be cost effective. However, we recommend a larger multicenter study for better results.
Keywords: Thyroid Gland